Parvalbumin and parvalbumin chandelier interneurons in autism and other psychiatric disorders - Juarez, Pablo; Martínez Cerdeño, Verónica (Frontiers in Psychiatry, 2022)
Parvalbumin (PV) is a calcium binding protein expressed by inhibitory fast-spiking interneurons in the cerebral cortex. By generating a fast stream of action potentials, PV+ interneurons provide a quick and stable inhibitory input to pyramidal neurons and contribute to the generation of gamma oscillations in the cortex. Their fast-firing rates, while advantageous for regulating cortical signaling, also leave them vulnerable to metabolic stress. Chandelier (Ch) cells are a type of PV+ interneuron that modulate the output of pyramidal neurons and synchronize spikes within neuron populations by directly innervating the pyramidal axon initial segment. Changes in the morphology and/or function of PV+ interneurons, mostly of Ch cells, are linked to neurological disorders. In ASD, the number of PV+ Ch cells is decreased across several cortical areas. Changes in the morphology and/or function of PV+ interneurons have also been linked to schizophrenia, epilepsy, and bipolar disorder. Herein, we review the role of PV and PV+ Ch cell alterations in ASD and other psychiatric disorders.